Unpacking the role of green smart technologies adoption, green ambidextrous leadership, and green innovation behaviour on green innovation performance in Malaysian manufacturing companies - Hossain, Mohammad Imtiaz; Teh, Boon Heng; Tabash, Mosab I.; Chong, Lee-Lee; Ong, Tze San (SAGE Publications, 2024)
Integrating the natural resource-based view theory, contingency theory and paradox theory, the current study investigates the impact of the green smart technologies adoption (GSTA) and green ambidextrous leadership (GAL) on green innovation performance (GIP), along with the mediating role of Green Innovation Behaviour (GIB). The research design for this study consists of a quantitative method, a positivism paradigm, a cross-sectional time horizon and a structured questionnaire survey. A total of 313 responses from Malaysian manufacturing firms were analysed using partial least squares-structural equation modelling (PLS-SEM). The findings reveal that GSTA, GAL and GIB positively impact GIP. Moreover, GIB mediates the association between GSTA and GIP, but there is no mediation observed in the GAL–GIP association. The results of this study provide valuable insights for policymakers, management and relevant stakeholders in developing countries on how to strike the right balance of exploitation and exploration leadership in uncertain and volatile market settings, while fostering GSTA and GIP. The adoption of GSTA and GAL improves manufacturing companies’ sustainability. Furthermore, these findings contribute to the Malaysian government’s commitment to the Nationally Determined Contribution towards the Paris Agreement, the Shared Prosperity 2030 vision and the proposed 15 key economic growth activities.